Looking into Pastoralism’s Future: Youth lead the 2026 Vision for Pastoralist Youth Consultation - Spinelli, Madison (International Livestock Research Institute, 2022)
All over the world, pastoralists derive their primary livelihood on rangelands that are estimated to cover more than 54% of the world’s land surface, most of which cannot sustain agricultural crops. They are significant contributors to countries’ economies, for example providing 90% of Mongolia’s agricultural GDP. In Africa alone, some 270 million pastoralists provide more than half of the continent’s meat and milk.